HOMER optimization of standalone PV/Wind/Battery powered hydrogen refueling stations located at twenty selected French cities - Oueslati, Fakher (Center of Biomass & Renewable Energy, Diponegoro University, 2023)
The current study proposes a model of autonomous Hydrogen Refuelling Stations (HRFS) installed on different sites in twenty French cities powered by renewable clean energy sources. The station is fully powered by photovoltaic (PV) panels, wind turbines with battery storage and involving an electrolyzer and hydrogen tank for producing and storing hydrogen. Using Homer simulation, three scenarios are investigated to propose an optimized model, namely Scenario 1 containing (PV-Wind-Battery) system, Scenario 2 with (Wind-Battery) technologies and Scenario 3 with (PV-Battery) components. The otimization process executed demonstrates very competitive levelized cost of energy (LCOE) and levelized cost of hydrogen (LCOH) especially for the third scenario solely based on PV power with LCOE in range 0.354-0.435/kWh and a LCOH varying within 13.5-16.5/kg, for all 20 cities. An average net present cost (NPC) value of 1,561,429 and 2,522,727 are predicted for the first and second architectures while least net present cost of 1,038,117 is estimated for the third combination solely based on solar power according to all sites considered. For instance, minimum values are obtained for Marseille city with LCOE= 0.354/kWh and a LCOH= 13.5 /kg in conformity with the minimum obtained value of NPC value of 886,464 with respect to the winner third scenario. In addition, more costly hydrogen production is expected for Grenoble city especially for scenario 1 and 2 where wind turbine technology is introduced. On another hand, thorough analysis of PV/wind hydrogen techno-economic operation is provided including improvements recommendations, scenarios comparison and environmental impact discussion.